PENGGUNAAN TONGKOL JAGUNG DAN PEPAYA SEBAGAI BAHAN DASAR PAKAN BUATAN BAGI PERKEMBANGAN LARVA Lalat Buah Bactrocera carambolae Drew dan Hancock (Diptera: Tephritidae) - Sri Heriza; Toto Himawan; Hagus Tarno (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
Research was conducted with preservation method in the plentiful number(rearing) in the Pest Laboratory, Plant Protection Department, Faculty ofAgriculture, University of Brawijaya. This research objective to get informationabout the use of corncob and papaya as basic material for larvae development.Design that was used in this research was complete randomized design with threerepeatition. This research used used five treatments that was food compositionwith wheat bran as control, corncob, corncob+coconut oil, papaya andpapaya+bread yeast. The result showed that corncob and papaya could be used asbasic material of artificial food for larvae of fruit fly development.Keywords: Corncob and papaya, artificial food, Bactrocera carambolae